Novel Precursors for the MOCVD of Molybdenum Nitride - Thiede, Tobias; Gwildies, Vanessa; Alsamann, Louay; Rische, Daniel; Fischer, Roland (ECS transactions, 2009)
Tungsten nitride and molybdenum nitride are electrically conducting refractory metal nitrides. Their applicability as novel gate electrode materials in CMOS technology is actually under investigation. MOCVD is one of the most prominent processes to deposit thin films of these materials. In order to improve the quality of MOCVD grown thin films it is important to optimize the chemical design of the employed precursors. Herein, we report on the synthesis of different imido-guanidinato-molybdenum complexes like [Mo(NtBu)2(X){(iPrN)2CNMe2}], (X = Cl, I, or N3). In particular we want to highlight that we were able to synthesize the new all nitrogen coordinated imido-amidinato-molybdenum complex [Mo(NtBu)2{(iPrN)2CMe}2]. The chemical and thermal properties of these new molybdenum compounds were investigated, to check their potential use as precursors for the MOCVD of molybdenum nitride.